Desire of Athlete and Non-athlete Students to Drugs Use - Saadi Sami; Sadigh Mahmoudi; Naseh Karimiani (The Society of Aging and Physical Activity (SAPA), 2014)
The purpose of this study was to evaluate and compare athlete and non-athlete students' tendency to drug use. 240 undergraduate students of University of Kurdistan with ages ranging from 19 to 23 years who had the experience of regular exercise (n = 120) and non-athlete ones (n = 120) were selected as the sample. Relapse Prediction Scale (RPS) was used for data collection. To analyze data, descriptive statistics (mean and standard deviation) and inferential statistics (independent t-test) were used at a significant level of p<0.05. All data were analyzed using SPSS. Study findings showed that there is a significant (p = 0.001 and p = 0.004, respectively) difference between athlete and non-athlete students in both desire (15.7±1.3 vs 28.1±2.0) and temptation (18.1±0.8 vs 30.4±1.5) to drugs abuse as athlete student had less both desire and temptation to drugs abuse than non-athlete. It is possible that engagement in sport activities have deterrent effect from some abnormal behavior such as drugs use.